1994
DOI: 10.1021/la00016a041
|View full text |Cite
|
Sign up to set email alerts
|

Three-Component Langmuir-Blodgett Films with a Controllable Degree of Polarity

Abstract: Two different series of mixed Langmuir-Blodgett (LB) films with a controllable degree of polarity, deposited on mica, have been studied by wetting and surface force techniques. Both series contain 50% eicosylamine (EA). Films of one series consist of EA, arachidic acid, and docosandioic acid, while those of the other consist of EA, 1-eicosanol, and 1,22-docosandiol. Carboxylic acid groups give lower contact angles than hydroxy groups. Concerning the stability of the LB films in aqueous solutions, repeated expo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
88
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(103 citation statements)
references
References 0 publications
11
88
0
Order By: Relevance
“…The common trend shows that the wettability of the surfaces apparently determines the accumulation kinetics of zoospore and diatoms, even though the terminating chemistries are entirely different. The general trend confirms the Berg limit which predicts inertness for contact angles below 65° [79,80]. Furthermore, the curve shows a minimum for the settlement of Ulva and Navicula on different SAMs at a contact angle of &35°.…”
Section: Surface Cues Can Trigger Permanent Adhesion Of Zoospores Of supporting
confidence: 81%
“…The common trend shows that the wettability of the surfaces apparently determines the accumulation kinetics of zoospore and diatoms, even though the terminating chemistries are entirely different. The general trend confirms the Berg limit which predicts inertness for contact angles below 65° [79,80]. Furthermore, the curve shows a minimum for the settlement of Ulva and Navicula on different SAMs at a contact angle of &35°.…”
Section: Surface Cues Can Trigger Permanent Adhesion Of Zoospores Of supporting
confidence: 81%
“…Comparable results were recently obtained in simulations, where the adhesion behavior was shown to depend crucially on the surface adhesion energy (19). A transition between dry adhesion and hydration repulsion was seen for typical surface contact angle values in the range of θ adh = 65°-85°, depending on the mechanical stiffness and the hydrogen-bonding capability of the surfaces (19), the values of θ adh being quite similar to those in experiments (15)(16)(17)(18).…”
supporting
confidence: 78%
“…In contrast, experiments probing the interactions between similar neutral surfaces with well-defined contact angles demonstrated that even hydrophilic surfaces exhibit short-range attractions not accountable by vdW forces down to typical adhesive contact angles of θ adh = 65°-80° (15)(16)(17)(18). Comparable results were recently obtained in simulations, where the adhesion behavior was shown to depend crucially on the surface adhesion energy (19).…”
mentioning
confidence: 69%
“…Arachidic acid (AA) was purchased from Merck and used as received. Eicosylamine (EA) was previously prepared according to Berg et al [14]. Chloroform was obtained from Merck and further purified by distillation in all glass apparatus.…”
Section: Experimental Materialsmentioning
confidence: 99%